The craft. Legacy [videorecording (Blu-Ray)] - Lister-Jones, Zoe; Spaeny, Cailee, 1997-; Adlon, Gideon, 1997-; Simone, Lovie, 1998-; Luna, Zoey (Sony Pictures Home Entertainment, 2020)
After learning about local legendary witch Nancy, a group of high school students ignores the cautionary part of her tale and forms a coven. The warning they didn't heed will come for them, however, as they lean into their newfound powers and discover the dark side of their craft.